Is hyponatremia in neonates with hypoxic ischaemic encephalopaty who underwent therapeutic hypothermia associated with poor neuro-developmental outcome at 12 months of ages? - Molotsi, Marang (Stellenbosch : Stellenbosch University, 2016)
Thesis (MMed)--Stellenbosch University, 2016.